Revision hip replacement for recurrent Hydatid disease of the pelvis: a case report and review of the literature - Chandrasekar Coonoor R; Neelapala Venkata SS; Grimer Robert J (Journal of Orthopaedic Surgery and Research, 2010)
Abstract A case of a large recurrent hydatid cyst involving the right ilium and right hip treated with excision of the cyst, Total hip replacement and revision of the acetabular component with a Tripolar articulation for cyst recurrence and acetabular component loosening is presented along with a review of the relevant literature. To our knowledge there is no reported case of Total Hip replacement and revision for hydatid disease involving the bony pelvis.